2022
DOI: 10.2196/30766
|View full text |Cite
|
Sign up to set email alerts
|

User Experience, Engagement, and Popularity in Mental Health Apps: Secondary Analysis of App Analytics and Expert App Reviews

Abstract: Background User experience and engagement are critical elements of mental health apps’ abilities to support users. However, work examining the relationships among user experience, engagement, and popularity has been limited. Understanding how user experience relates to engagement with and popularity of mental health apps can demonstrate the relationship between subjective and objective measures of app use. In turn, this may inform efforts to develop more effective and appealing mental health apps a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 40 publications
0
27
1
1
Order By: Relevance
“…However, since the MARS does not consider the number of different features of MHAs in functionality evaluation [21], comparison between the functionality of MHAs with comprehensive features and MHAs with limited features is di cult. Also, in this study, the user score was correlated with the overall score of MARS as well as the subjective quality score of the MHA, which was in contrast to previous studies that reported no correlation between the MARS score and the user score [24,26,34,35]. Given that users often rely on user ratings when choosing an app to download [22], this is an encouraging nding that there is a correlation between user ratings and MARS ratings for Persian maternity care MHAs.…”
Section: Discussioncontrasting
confidence: 86%
“…However, since the MARS does not consider the number of different features of MHAs in functionality evaluation [21], comparison between the functionality of MHAs with comprehensive features and MHAs with limited features is di cult. Also, in this study, the user score was correlated with the overall score of MARS as well as the subjective quality score of the MHA, which was in contrast to previous studies that reported no correlation between the MARS score and the user score [24,26,34,35]. Given that users often rely on user ratings when choosing an app to download [22], this is an encouraging nding that there is a correlation between user ratings and MARS ratings for Persian maternity care MHAs.…”
Section: Discussioncontrasting
confidence: 86%
“…Similarly, usability has been reported as important for promoting engagement. Acceptability and engagement are critical elements of mental health apps that support users [ 73 ]. However, it is recognized that operationalizing meaningful app engagement is not straightforward, as many downloaded apps are never used and more work is needed to define sustained engagement, what leads to it, and how to create products that achieve it [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acceptability and engagement are critical elements of mental health apps that support users [ 73 ]. However, it is recognized that operationalizing meaningful app engagement is not straightforward, as many downloaded apps are never used and more work is needed to define sustained engagement, what leads to it, and how to create products that achieve it [ 73 , 74 ]. Further research may explore characteristics facilitating initial use, continued use, and the implications of changing the treatment structure during an intervention (eg, Do individuals find it motivating or overwhelming?).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several participants mentioned wanting a social media component to help them feel more engaged. The incorporation of social media has been shown to improve app engagement [ 98 ] and may help to improve long-term app use [ 99 ]; therefore, we may also develop and include social features in future iterations of RuminAid.…”
Section: Discussionmentioning
confidence: 99%